The Effect of Sustainability Disclosure, Good Corporate Governance Mechanism and Intellectual Capital on Return on Assets - Yuliana, Nita; Utami, Wiwik (Archives of Business Research, 2022)
This study aims to examine the effects of disclosure of sustainability, corporate governance mechanisms, and intellectual capital on the return on assets. The population of this study is banking companies listed on the IDX in 2016-2019. The samples were selected based on the criteria of 27 companies over a 4-year period, so that 108 samples were obtained. Regression analysis method on panel data using EViews 12 The results of this study indicate that sustainability disclosure has no significant effect on ROA, frequency of board of Commissioners meetings has a positive and significant effect on ROA, institutional ownership has no significant effect on ROA, and intellectual capital has a positive and significant effect on ROA.